Peran E-commerce dalam Meningkatkan Resiliensi Bisnis diera Pandemi - Mohammad Orinaldi (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2020)
Online business based on E-commerce has long been known since before the Covid-19 pandemic, as evidenced by 15.08% of business people have used digital platforms in developing their businesses. E-commerce is a public need that has increased drastically during the Covid-19 pandemic. E-commerce platform users increased by 38.3% as long as social policies were implemented. This study aims to analyze the role of E-commerce in maintaining business during an economic recession. The research method used is literature review. The results of the discussion show that the types of small businesses and MSMEs are sectors that are quite affected by Covid-19 . The business sector will not be able to survive a period of economic recession if it does not adapt to technological developments towards the online market. E-commerce is key in the creation of an online market, so that it can mediate interactions between producers or sellers and consumers. E-commerce can maintain a balance of production and consumption because trading activities are maintained over a long distance. This balance can encourage economic growth in a more positive direction. E-commerce is able to help business actors to maintain their business activities, as well as to help consumers maintain purchasing power to meet their needs.